Are There Any Distinctions Between the Sources of Well-Being for Students in Rural and Urban Areas? - Ros Mayasari; Khairunnisa Syamsu; Nani Restati Siregar (Indigenous: Jurnal Ilmiah Psikologi, 2024)
Although research on well-being has been extensively documented by experts, there is a paucity of literature addressing it from a geographical background perspective, especially in the rural-urban context. Therefore, this study aims to examine students' experiences related to well-being sources, considering the geographical background of students from rural and urban areas. The research employs a case study research design. Data collection is conducted through interviews with high school students in Southeast Sulawesi, Indonesia. Data analysis is carried out using thematic analysis and the school well-being model by Konu and Rimpela. The research findings reveal no differences in the sources of well-being between students from schools in urban and rural areas, except for the relationship between teachers and students, which was found to be more closely related to urban students than rural students. Social relationships among school members, school facilities and conditions, participation in school organizations and extracurricular activities, consistent enforcement of school rules, and the fulfillment of self-identity are sources of happiness for students in rural and urban settings. Similarly, this study expands the Konu and Rimpela model by incorporating the provision of Wireless Networking (Wi-Fi) and the aesthetic quality of school locations under the dimension of having. Ultimately, this research implies that creating harmonious conditions among school members and arranging the aesthetic aspects of the school environment and Wi-Fi facilities are crucial factors to be considered in efforts to nurture and enhance students' well-being.